2001
DOI: 10.1016/s0014-5793(01)02955-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between two adapter proteins, PAG and EBP50: a possible link between membrane rafts and actin cytoskeleton

Abstract: Phosphoprotein associated with GEMs (PAG), also known as Csk-binding protein (Cbp), is a broadly expressed palmitoylated transmembrane adapter protein found in membrane rafts, also called GEMs (glycosphingolipid-enriched membrane microdomains). PAG is known to bind and activate the essential regulator of Src-family kinases, cytoplasmic protein tyrosine kinase Csk. In the present study we used the yeast 2-hybrid system to search for additional proteins which might bind to PAG. We have identified the abundant cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 14 publications
1
85
1
Order By: Relevance
“…This result has been clearly demonstrated for the ␤ adrenergic receptor, as stimulation of the human airway mucosa with the nonspecific ␤ receptor agonist isoproterenol activates CFTR-dependent Cl Ϫ transport in vivo (6). Biochemical studies have demonstrated that the C-termini of CFTR and ␤ 2 adrenergic receptors (␤ 2 AR) possess PDZ binding motifs, and these domains contribute to interactions between these membrane proteins (7-9) and cytoskeletal proteins (10) that are important for channel regulation (11,12) and trafficking (13,14). No studies, however, have conclusively demonstrated that interactions of this sort contribute to CFTR regulation by surface receptors.…”
mentioning
confidence: 87%
“…This result has been clearly demonstrated for the ␤ adrenergic receptor, as stimulation of the human airway mucosa with the nonspecific ␤ receptor agonist isoproterenol activates CFTR-dependent Cl Ϫ transport in vivo (6). Biochemical studies have demonstrated that the C-termini of CFTR and ␤ 2 adrenergic receptors (␤ 2 AR) possess PDZ binding motifs, and these domains contribute to interactions between these membrane proteins (7-9) and cytoskeletal proteins (10) that are important for channel regulation (11,12) and trafficking (13,14). No studies, however, have conclusively demonstrated that interactions of this sort contribute to CFTR regulation by surface receptors.…”
mentioning
confidence: 87%
“…Thus, lipid rafts can control NT growth in a different way, as well. In lymphoid cells, the PM rafts usually contain raft-associated adaptor membrane proteins, such as PAG or EBP50 ezrin-binding protein, that may mediate dynamic connections of the PM to the actin filament network [53,54]. Binding of pleckstrin homology domain proteins is also under control of cholesterol level and thus responsible for the dynamic coupling to the actin cytoskeleton [15].…”
Section: Discussionmentioning
confidence: 99%
“…The PDZ-binding motif of Cbp may mediate the regulation of RhoA activation Cbp is known to interact via its C-terminal PDZbinding motif with EBP50, which in turn binds to ERM family (Brdickova et al, 2001;Itoh et al, 2002). ERM proteins have been implicated in the regulation of cytoskeleton organization and Rho GTPases activation (Bretscher, 1999;D'Angelo et al, 2007;Niggli and Rossy, 2008).…”
Section: The Effects Of Cbp Knockdown On the Activation Of C-src Mapmentioning
confidence: 99%
“…Here, we found that the PDZ-binding motif of Cbp might be associated with RhoA activation. Cbp is well known to bind to EBP50 via this PDZ-binding motif (Brdickova et al, 2001;Itoh et al, 2002). EBP50 is a cytosolic protein that links membrane proteins with ERM proteins, which directly interact with actin cytoskeletons once activated (Reczek et al, 1997;Bretscher, 1999).…”
Section: Involvement Of Cbp In Renal Cell Carcinogenesis X Feng Et Almentioning
confidence: 99%
See 1 more Smart Citation